Inflation, Taxation, and Corporate Behavior - Gordon, Roger H. (Quarterly Journal of Economics, 1984)
Under the U. S. tax law, taxable income differs systematically from economic income when there is inflation. For example, nominal interest payments and nominal capital gains are taxable or tax deductible, and depreciation allowances are based on historic rather than replacement costs. Therefore, even fully anticipated inflation can have real effects. The purpose of this paper is to investigate to what degree an increase in the inflation rate, given these differences between taxable and economic income under existing tax law, ought to change corporate investment and financial policy, and cause capital gains or losses to existing owners of corporate equity.